RESPON PERTUMBUHAN DAN HASIL PADI INPARI IR NUTRI ZINC TERHADAP KOMPOSISI PUPUK UREA DAN PUPUK HIJAU PADA TANAH ALUVIAL - Aynun Syahira; Tantri Palupi; Dini Anggorowati (Fakultas Pertanian, Universitas Janabadra, 2024)
high Zn content than other varieties. The research objective was to determine the best dose of urea fertiliser composited with green manure on the growth and yield of Inpari IR Nutri Zinc rice on alluvial soil. The research was conducted at Jalan Sepakat 2, Pontianak from August to December 2023. This study used a completely randomised design consisting of 1 factor. The factor tested was the application of urea fertiliser with green manure composition. consists of 5 treatment levels: (A) 100 kg/ha urea and 500 kg/ha green manure, (B) 150 kg/ha urea and 450 kg/ha green manure, (C) 200 kg/ha urea and 400 kg/ha green manure, (D) 250 kg/ha urea and 350 kg/ha green manure, and (E) 300 kg/ha urea, with 5 replications. The observed variables were: plant height, number of tillers, number of productive tillers, leaf blade colour index, plant dry weight, panicle length, number of filled grains per panicle, number of empty grains per panicle, number of panicles per clump, 1000 seed weight, grain weight per clump, and grain loss per panicle. The results showed that the composition of the doses of urea and green manure 250 and 350 kg/ha can streamline the use of urea fertiliser by 17% equivalent to 50 kg/ha in producing growth and yield of Inpari IR Nutri Zinc rice plants on alluvial soils.